Wujudkan Pendidikan Merdeka Belajar, Stop Penindasan dan Perundungan Pada Siswa - Putri, Destia; Putra, Dodi Pasila; Novelia, Tesy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education is a bridge for a person to achieve all their dreams, this is because the knowledge and knowledge contained in education plays an important role in every human activity, starting from academics, creativity, character and a person's personality will be formed through this educational activity. Based on Law no. 20 of 2003 concerning national education states that the aim of education is to create individuals with noble character. However, in fact, the biggest problem experienced by education in Indonesia is cases of bullying which have never been resolved. The aim of this research is to find out to what extent independent learning education is able to overcome and direct so that cases of bullying do not occur again in schools. The research method is phenomenology based on current events, this type of research uses a qualitative descriptive approach, data collection is based on observation, direct observation in the field, as informant sources, teachers and students. The results of this research illustrate that cases of bullying that have occurred in schools can be overcome if independent learning education is realized or fully implemented. In this case, there is also a way for guidance counselors to minimize bullying behavior, namely by implementing classical guidance services using sociometric administration to find out what the state of children's social relations are in the classroom and implementing individual counseling services according to the needs of students.